LA PODCASTFERA ESPAÑOLA COMO COMUNIDAD DE APRENDIZAJE NO FORMAL. COMPETENCIAS Y ESTRATEGIAS EDUCOMUNICATIVAS DESARROLLADAS POR LOS PODCASTERS INDEPENDIENTES - Dr. David GARCÍA-MARÍN (Fonseca, Journal of Communication, 2023)
Born in 2004, Spanish independent podcasting has managed to build an online community of communicators and users that can be regarded as an intermediate socialization mechanism that connects individual production with social connection. Through research developed in three phases by applying techniques of ethnographic observation, documentary analysis and in-depth interviews with podcasters, the aim of the study is to build a taxonomy of the set of media and digital competences that podcast makers acquire within this community and how the incorporation of such knowledge is produced.